Keadilan Berpoligami dalam Persepektif Psikologi - Azwar Fajri (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
Justness of polygamy in the Qur-an is only explained to the extent of satisfying the material needs without further explanation aboutits application. While the immaterial justice is impossible to be reached. From psychological outlook, the fulfillment of material justness is designed and planned by all parties involved until a form of just commitment can be reach. But still the immaterial justice cannot also be actualized, Although, implicitly some attempts have been made through committing together on the agreements that attentively respect on the agreements, neutral and keeping trust of each party.